2010
DOI: 10.1366/000370210792434314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Use of Volume Fractions with other Measures of Concentration for Quantitative Spectroscopic Calibration Using the Classical Least Squares Method

Abstract: Since the commercial development of modern near-infrared spectroscopy in the 1970s, analysts have almost invariably used units of weight percent as the measure of analyte concentration, due largely to the historical precedent from other analytical methods, including other spectroscopic techniques. The application of the CLS algorithm to a set of binary and ternary liquid mixtures reveals that the spectroscopic measurement sees the sample differently; that the measured absorbance spectrum is in fact sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…In the Cooman plot, the simulated F 1 hybrid [ Figure 6(B), filled triangles] clustered tightly between the PEE and PCH parents and was close in distance to the model centres of the two pure parents. This is as expected in the case of an unreactive mixture of equal parts of foliage from the pure parents in a manner similar to a mixture of ethanol and water, 48 and indicates that a favourable bias in discrimination is introduced by creating simulated F 1 hybrids by simple mixing of foliage from the parents. By contrast, the actual F 1 hybrid [ Figure 6(A), open circles] showed much more scatter with most individual samples lying at greater distances from the model centres than the simulated hybrids.…”
Section: Discussionsupporting
confidence: 75%
“…In the Cooman plot, the simulated F 1 hybrid [ Figure 6(B), filled triangles] clustered tightly between the PEE and PCH parents and was close in distance to the model centres of the two pure parents. This is as expected in the case of an unreactive mixture of equal parts of foliage from the pure parents in a manner similar to a mixture of ethanol and water, 48 and indicates that a favourable bias in discrimination is introduced by creating simulated F 1 hybrids by simple mixing of foliage from the parents. By contrast, the actual F 1 hybrid [ Figure 6(A), open circles] showed much more scatter with most individual samples lying at greater distances from the model centres than the simulated hybrids.…”
Section: Discussionsupporting
confidence: 75%
“…From this procedure it was found that the differences in the actual volumes of the mixture samples and the sum of the volumes of the pure components used for sample preparation was l minimal, and the coefficients of variation for the actual volumes of the mixture samples were 0.43% and 0.51% for system 1 and system 2, respectively. Furthermore, in their publications [10,11,12,13] Mark et al claimed, that for NIR calibrations the use of volume percentage—corresponding to the scaled volume fraction concentration unit of Beer’s law—is the better approach than weight percentage. In what follows we will show, that this statement is not supported by the results of the investigated multicomponent systems.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this work, apart from comparing the impact of molecular interactions in liquid multicomponent systems on the results obtained by the two different types of spectroscopies, a further topic of this publication are the effects of these structural phenomena on the performance of two different multivariate evaluation routines (PLS and CLS regression) for the quantitative analysis of the investigated liquid three-component systems. Last but not least—and with reference to previous studies by Mark et al [10,11,12,13]—we have tried to shed light on the consequences of using different concentration units (%V and %W) for the quantitative analysis of the described multicomponent systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, discrepancies as large as 10-15% were found to exist between the computed concentrations and the ''known'' concentrations of the samples. The details can be found in Mark et al 2 or in the other above-listed references. A summary of the explanation follows.…”
Section: Resultsmentioning
confidence: 99%
“…But it seems that very few chemists or spectroscopists (or chemometricians) do. An abbreviated mathematical proof of that fact, however, can be found in Mark et al 2 In modern day spectroscopic analysis, the overwhelmingly common concentration units used are weight percents: 100 times the weight fractions. For chemists, that ordinarily does not matter.…”
Section: Resultsmentioning
confidence: 99%